Organic management for yams (Dioscorea spp.) intercropped in coconut (Cocos nucifera) plantation: Evidences from a validation trial in the coastal humid tropics of Kerala, India - SUJA, G; SUBRAMANIAN, P; SUREKHA, R; JAGANATHAN, D; MARIA, C LINTU; RAJ, RAKHI K (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted under Network Project on Organic Horticulture during 2015–17 (April-January) at ICAR-Central Plantation Crops Research Institute (ICAR-CPCRI), Kasaragod, to validate the ICAR-CTCRI developed organic farming technologies in yams under intercropping in an organically raised mature coconut garden (>48 years). Three species of Dioscorea [(greater yam (D. alata), lesser yam (D. esculenta) and white yam (D. rotundata)] were tested under four production systems, viz. traditional, conventional, integrated and organic, and replicated thrice in split plot design in a mature coconut garden. Organic practice was similar to conventional as revealed from the identical impacts on yield, tuber quality and soil chemical properties. Yield under organic management was 98.6% of conventional farming. D. alata and D. esculenta were more responsive (+8 to 10%) to organic management, but organic management lowered yield by 30% in dwarf white yam (D. rotundata). The organic farming package comprising farmyard manure, green manure cowpea, neem cake and ash resulted in higher available N, exchangeable Ca and available Zn in soil and significant improvement in K, higher P and Mg contents in yam tubers. However, the highest profit was realized from coconut + D. alata in integrated system (`1,87,057/ha). Among yams, greater yam (D. alata) was the most productive and profitable under organic management (`1,46,634/ha) in intercropping set up.